PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI KELAS VIII SMPN 1 PANEKAN - sulastri lastri; Joko Widianto; Siti Sundari (JPPG : Jurnal Pengembangan Profesi Guru, 2023)
Abstract The background of this research was obtained from the results of initial observations, namely the low ability to think critically and the low achievement of students learning science at SMPN 1 Panekan. This research is a classroom action research carried out in two cycles. The action of this research is the application of the Problem Based Learning model to the material of light and optical devices. The purpose of this action is to improve learning outcomes and critical thinking of SMPN 1 Panekan students. The subjects of this study consisted of 31 students of class VIII B at Panekan 1 Public Middle School. The object of this research is an increase in critical thinking attitudes and science learning outcomes after receiving special actions in the learning process. The data needed in this study were obtained through observation and tests. From this study, it was found that there was an increase in critical thinking skills from the initial condition of an average of 59.62 to 74.25 in cycle I and increased to 82.56 in cycle II. Knowledge learning outcomes increased starting from the initial average value of 56.93, to 76.45 in cycle I, increasing to 85.64 in cycle II.